SKARN MINERALIZATION MODELLING AND ITS EFFECT ON MINERAL RESOURCES OF BATU HIJAU CU-AU PORPHYRY DEPOSIT, SUMBAWA, WEST NUSA TENGGARA - Naruputro, Agung
Batu Hijau Cu-Au porphyry is one of the largest porphyry deposits in Indonesia. Batu Hijau mineral reserve were firts published in 1996, with 914 million tons of ore, 0.53% copper garde (10.58 billion pounds of copper metal) and 0.40 g/t gold grade (3.19 million ounces of gold metal). Batu Hijau deposit has been mined for 23 years using the open pit mining method. The mining has entered the final phase (phase 7). Mineral reserves of phase 7 are 203 million tons of ore with 0.48% copper grade (2.2 billion pounds of copper metal) and 0.46 g/t gold grade (3 million ounces of gold metal). Resource development drilling was conducted in 2018-2020 to assess the potential of mineral resource after phase 7 with a total of 102 holes and a total length of 60,000 m. The drilling provided significant additional data to identify the skarn at Batu Hijau. Previous study was conducted after obtaining skarn data from 2003 drilling and the distribution of skarn mineralization was still not well understood and modeled. Descriptive statistical analysis of the copper and gold grade of the skarn at Batu Hijau shows the skarn mineralization has an average copper grade of 0.24% and gold grade of 0.19 g/t. Skarn gold and copper grades has a different distribution compared to other rock types. The copper grade of skarn is higher than young tonalite, while the gold grade of Skarn is higher than Diorite and Volcanic rocks. Three-dimensional modeling of the skarn resulted in a radial shape of the skarn mineralization but not symmetrical on all sides with the west and northwest sides being larger than the east and south sides. While the northeast side is cut by the northwest - southeast trending faults. The distribution of skarn at Batu Hijau in a very deep elevations, the lowest elevation is -645 m and the highest is -45 m. The Skarn model shows correlation with intermediate tonalite, secondary biotite alteration and northwest - southeast trending faults. Skarn is located along the contact of the intermediate tonalite, mainly on the western side with volcanic rock. The skarn distribution is also in the outer part of the secondary biotite alteration. The Skarn is associated with five major northwest - southeast trending faults, the Roni, Kerinci and Katim Splay faults which cut the skarn on the north side and may explain the discontinuous skarn in the north. The separate skarn body in the northeast correlates with the Ceremai fault. The total mineral resource of Batu Hijau Skarn is 314 million tons with Cu grade of 0.31% and Au grade of 0.25 g/t. While the total measured and indicated resource of skarn is 267 million tons with Cu grade of 0.32% and Au grade of 0.26 g/t Au. The influence of skarn modeling in the Batu Hijau mineral resource estimation has a positive impact of 2.7 million tons of ore, the same average copper and gold grades, with contained metal of 7 million pounds of copper and 162 thousand ounces of gold in the measured and indicated resource classifications. The differences is very small compared to the total Batu Hijau deposit, which is 0.2% of the total Batu Hijau mineral resources for the measured and indicated classifications. However, the use of the Skarn domain can represent the actual geological conditions when the resource estimation is carried out although the affect is not significant to the overall Batu Hijau mineral resources.